2000
DOI: 10.7863/jum.2000.19.9.633
|View full text |Cite
|
Sign up to set email alerts
|

Value of prone positioning in the ultrasonographic diagnosis of gallstones: prospective study.

Abstract: To determine prospectively the value of prone/postprone positioning in the sonographic detection of gallstones, 682 patients were scanned in the recumbent, erect, and prone or postprone positions. The gallbladder was evaluated for an intraluminal hyperechoic focus, shadowing, and gravitational dependence and was identified in 679 patients. Among these, 28% had cholelithiasis. In five cases, prone positioning alone revealed gallstones. In 11 of 140 cases, gravitational dependence was only seen with prone scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The main purpose of this paper is to demonstrate whether supplementary anatomical and/or pathological detail may be available using a previously unreported technique. 5 Although the mean additional length of gallbladder demonstrated using the reverse decubitus position in this series of patients was small at 0.9 cm (in some cases very small at 0.1 cm), in all subjects in this study some additional anatomical detail was demonstrated; in some subjects a significant additional gallbladder length of up to 2 cm was demonstrated. It is possible that these appearances are partially attributable to geometric variations, but this influence does not seem likely as many of the LAO scans were performed using a right-sided approach.…”
Section: Resultsmentioning
confidence: 45%
“…The main purpose of this paper is to demonstrate whether supplementary anatomical and/or pathological detail may be available using a previously unreported technique. 5 Although the mean additional length of gallbladder demonstrated using the reverse decubitus position in this series of patients was small at 0.9 cm (in some cases very small at 0.1 cm), in all subjects in this study some additional anatomical detail was demonstrated; in some subjects a significant additional gallbladder length of up to 2 cm was demonstrated. It is possible that these appearances are partially attributable to geometric variations, but this influence does not seem likely as many of the LAO scans were performed using a right-sided approach.…”
Section: Resultsmentioning
confidence: 45%
“…When performing local ablation therapies, it is important to obtain a better sonographic window and plan a safe puncture route. Various body positions have been attempted for better visualization of the entire liver during US examinations [ 31 , 38 , 39 ]. Among various body positions, supine, right half side lying, left half side lying, head up, and upright were mainly used according to the site of the tumor and the patient’s body size empirically.…”
Section: Discussionmentioning
confidence: 99%
“…The value of using upright and prone positioning to detect gallstones and show mobility has been recognized by experienced radiologists and sonographers for many years. 4,8 The 2017 American College of Radiology Practice Parameter for the Performance of an Ultrasound Examination of the Abdomen and/or Retroperitoneum specifies that the gallbladder should be viewed in the supine position and when feasible in the decubitus position (RLD or LLD not specified). It also states that "Other positions such as erect or prone imaging may be helpful to evaluate the gallbladder and its surrounding areas completely."…”
Section: Discussionmentioning
confidence: 99%